2017
DOI: 10.1371/journal.pone.0176851
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer stemness and anti-invasive activity of bitter taste receptors, TAS2R8 and TAS2R10, in human neuroblastoma cells

Abstract: Neuroblastoma (NB) originates from immature neuronal cells and currently has a poor clinical outcome. NB cells possess cancer stem cells (CSCs) characteristics that facilitate the initiation of a tumor, as well as its metastasis. Human bitter taste receptors, referred to as TAS2Rs, are one of five types of basic taste receptors and they belong to a family of G-protein coupled receptors. The recent finding that taste receptors are expressed in non-gustatory tissues suggest that they mediate additional functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 64 publications
(84 reference statements)
6
53
0
Order By: Relevance
“…This suggests that TAS2R10 may be a key trigger of host defense pathways. Previous observations showing its anticancer activities and regulation of smooth muscle relaxation are consistent with our results 21,22 . Other studies showed that TAS2Rs can activate the robust calcium‐dependent secretion of antimicrobial peptides (AMPs), including β‐defensin 1 and 2, from epithelial cells in the respiratory tract 9,27,28 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that TAS2R10 may be a key trigger of host defense pathways. Previous observations showing its anticancer activities and regulation of smooth muscle relaxation are consistent with our results 21,22 . Other studies showed that TAS2Rs can activate the robust calcium‐dependent secretion of antimicrobial peptides (AMPs), including β‐defensin 1 and 2, from epithelial cells in the respiratory tract 9,27,28 .…”
Section: Discussionsupporting
confidence: 92%
“…As such, it may largely contribute to the overall bitter tasting ability and exert broad effects on the human body. Despite several functional studies, 21,22 the detailed functions of TAS2R10 are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…It may be speculated that TAS2R10 is able to perform numerous biological functions. Recent studies have indicated other functions of TAS2R10 than bitterness-sensing (10). However, only two functions have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TAS2R10 was reported to mediate relaxation of vascular smooth muscles (9). Of note, TAS2R10 also has a tumor suppressor role in human neuroblastoma cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…Expressional deregulation of many other proteins are also causally linked to the dedifferentiation of nonstem cancer cells and formation of iCSCs [118,[145][146][147] . For instance, Lamin A/C, the type V intermediate filaments of nuclear lamina, is often reduced or absent in proliferative cells of various tumors [148,149] .…”
Section: Induced Cscs and Therapy Resistancementioning
confidence: 99%